HUBUNGAN ANTARA CITRA MEREK MOBIL SUZUKI DENGAN KEPUTUSAN PEMBELIAN PADA KONSUMEN DI DEALER SUMBER BARU MOBIL PURWOKERTO - Janah, Maslichah Raichatul (Universitas Sahid Surakarta, 2013)
More and more automotive companies that operate with a variety ofproducts on offer has enabled people to make choices according to their needs and options , where the importance of the brand . Brand image can not be built on lies information . A consumer in making a purchase decision is not denied if always pay attention to the image of a brand and its quality , but for mepertahankan and enhance the image of a brand is not easy to have great effort for each company. This research aims to determine the relationship between Suzuki brand image with the consumer purchase decision in Purwokerto Car Dealers New Source . Subjects in this study isthat consumers in the New Source Car dealer located in Navan area totaling 70 people. The sampling technique used is incidental non- random sampling . While the data collectioninstruments used were brand image scale and scale pebelian decision. Moent product analysis results showed a correlation of r = 0.393 with p < 0.01, indicating that there is a significant positive relationship between brand image obil Suzuki withpurchasing decisions